Allogeneic hematopoietic stem cell transplantation for the treatment of BCR-ABL1-negative atypical chronic myeloid leukemia and chronic neutrophil leukemia: A retrospective nationwide study in Japan. (December 2018) - Itonaga, Hidehiro; Ota, Shuichi; Ikeda, Takashi; Taji, Hirohumi; Amano, Itsuto; Hasegawa, Yuichi; Ichinohe, Tatsuo; Fukuda, Takahiro; Atsuta, Yoshiko; Tanizawa, Akihiko; Kondo, Takeshi; Miyazaki, Yasushi
Highlights: Allo-HSCT offered a potential for cure in aCML and CNL during not in CR. Among aCML patients, ≥5% myeloblasts in PB at HSCT may correlate with worse outcome. Allo-HSCT using alternative donor might be a considerable option for aCML and CNL. Abstract: Atypical chronic myeloid leukemia (aCML) and chronic neutrophilic leukemia (CNL) are rare BCR-ABL1 fusion gene-negative myeloid neoplasms with a predominance of neutrophils. Since no standard therapeutic strategy currently exists for these diseases, we retrospectively evaluated the outcomes of allogeneic hematopoietic stem cell transplantation (allo-HSCT) for aCML and CNL. Data from 14 aCML and 5 CNL patients as their diagnoses were collected using a nationwide survey. Allo-HSCT was performed between 2003 and 2014. Preconditioning regimens included myeloablative (n = 15), reduced-intensity (n = 3), and non-myeloablative (n = 1) regimens. Transplanted stem cells were obtained from HLA-matched related donors (n = 5) and alternative donors (n = 14). Neutrophil engraftment was successfully achieved in 17 patients. One-year overall survival rates (OS) were 54.4% (95% confidence interval [CI], 24.8 to 76.7%) and 40.0% (95% CI, 5.2 to 75.3%) in patients with aCML and CNL, respectively. Among aCML patients, 1-year OS were 76.2% (95% CI, 33.2 to 93.5%) and 20.0% (95% CI, 0.8 to 58.2%) in patients with <5% myeloblasts (n = 9) and ≥5% myeloblasts (n = 5) in peripheral blood before allo-HSCT, respectively. These results suggest that allo-HSCT achieves long-term survival in patients with aCML and CNL. Better pre-transplant management is required to improve the outcomes of aCML patients with ≥5% blasts in peripheral blood.